Revised decision on the waterproofing work in the bathroom floors and rooftop landscaping area - Brac University (Brac University, 2023)
This record consists of general correspondence regarding revised decision on the waterproofing work in the bathroom floors and rooftop landscaping area of BRAC University new campus project.